Effective learning model bases problem based learning and digital mind maps to improve student’s collaboration skills - Nurkhairo Hidayati; Siti Zubaidah; Sri Amnah (International Journal of Evaluation and Research in Education (IJERE), 2023)
Student’s collaboration skills are still low while this skill is important for students. The selection of an active learning model is an attempt to overcome this problem. This study aimed to investigate the effects of problem based learning (PBL) and integrated PBL digital mind maps (DMM) on university students’ collaboration skills. This quasi-experimental study employed a pretest-posttest control group design. The participants consisted of 103 students majoring in biology education from Riau, Indonesia. Each of the classes was randomly picked to act as the PBL group, integrated PBL-DMM group, and traditional group. The students’ collaboration skills were observed using an observation sheet which contained aspects of responsibility, respect, contribution, organize work and work as a whole team. The data obtained were analyzed using analysis of covariance (ANACOVA) and least significance different (LSD) test. The ANACOVA results demonstrated some significant changes in both comparison groups: PBL and integrated PBL-DMM. In other word, learning models had an effect on students’ collaboration skills. However, the LSD test proved that both learning models were not significantly different in improving students’ collaboration skills, despite the fact that the students in the integrated PBL-DMM model class could perform better than those of PBL. Therefore, educators may either use PBL or integrated PBL-DMM in the classroom.